Planting An Entrepreneurial Soul Through Activities Cooking Class - Fuadul Mustofa; Lailatul Rohmah; Erni Munastiwi (Institut Agama Islam Negeri Madura, 2024)
Instilling an entrepreneurial spirit in early childhood is an important step in forming independent and innovative attitudes, skills and thoughts. Various ways can be done, including encouraging creativity and innovation, for example cooking class activities. This study aims to explore the influence of